Green processes for nanotechnology from inorganic to bioinspired nanomaterials - Basiuk, Vladimir A.; Basiuk, Elena V. (Springer International Publishing, 2015)
Provides the state-of-the-art survey of green techniques in the preparation of different classes of nanomaterials, with an emphasis on the use of renewable sources. Key topics covered include fabrication of nanomaterials using green techniques as well as their properties and applications, the use of renewable sources to obtain nanomaterials of different classes, from simple metal and metal oxide nanoparticles to complex bioinspired nanomaterials, economic contributions of nanotechnology to green and sustainable growth, and more. This is an ideal book for students, lecturers, researchers and engineers dealing with versatile (mainly chemical, biological, and medical) aspects of nanotechnology, including fabrication of nanomaterials using green techniques and their properties and applications. This book also: Maximizes reader insights into the design and fabrication of bioinspired nanomaterials and the design of complex bio-nanohybrids Covers many different applications for nanomaterials, bioinspired nanomaterials, and complex bio-nanohybrids, with an emphasis on biomedical applications Broadens readers? understanding of environmentally-friendly techniques for the synthesis of nanomaterials